Tricuspid regurgitation after cardiac resynchronization therapy: evolution and prognostic significance - Stassen Jan; Galloo Xavier; Hirasawa Kensuke; Marsan Nina A.; van der Bijl Pieter; Delgado Victoria; Bax Jerome J. (OXFORD UNIV PRESS, 2022)
Aims Tricuspid regurgitation (TR) is common in patients with heart failure (HF) and is associated with worse outcome. This study investigated the effect of cardiac resynchronization therapy (CRT) on TR severity and long-term outcome. Methods and results Tricuspid regurgitation severity was assessed at baseline and 6 months after CRT implantation, using a multiparametric approach. Patients were divided into four groups: (i) no or mild TR without progression; (ii) no or mild TR with progression to significant (moderate-severe) TR; (iii) significant TR with improvement to no or mild TR; and (iv) significant TR without improvement. The primary endpoint was all-cause mortality. A total of 852 patients (mean age 65 +/- 11 years, 77% male) were included. At baseline, 184 (22%) patients had significant TR, with 75 (41%) showing significant improvement at 6-month follow-up. After a median follow-up of 92 (50-137) months, 494 (58%) patients died. Patients with significant TR showing improvement at follow-up had better outcomes than those showing no improvement (P = 0.016). On multivariable analysis, no or mild TR progressing to significant TR [hazard ratio (HR) 1.745; 95% confidence interval (CI): 1.287-2.366; P < 0.001] and significant TR without improvement (HR 1.572; 95% CI: 1.198-2.063; P = 0.001) were independently associated with all-cause mortality, whereas significant TR with improvement at follow-up was not (HR: 1.153; 95% CI: 0.814-1.633; P = 0.424). Conclusion Improvement of significant TR after CRT is observed in a substantial proportion of patients, highlighting the potential benefit of CRT for patients with HF having significant TR. Significant TR at 6 months after CRT is independently associated with increased long-term mortality.